Cyber Public Relations Activities of Depok City Diskominfo in Building a Positive Image - Ghina Nur Afifah; Amellia Alfidhdhah Yanti (CHANNEL: Jurnal Komunikasi, 2022)
With technological development, all government agencies are always required to strive to reach their citizens in the national and regional scope. Depok City Diskominfo is a regional government agency that has followed the development of the technological era by carrying out cyber PR activities. One of the goals is to build a  positive image. However, this is inseparable from complaints from the  Depok city residents as its stakeholders. This research was conducted to determine the cyber  PR activity of Depok City Diskominfo in building a positive image. This research uses a descriptive qualitative method based on four characteristics of cyber. Data collection is done through interviews, literature studies, and documentation to gather information about these activities. The study results found that the cyber PR activities that the Depok City Diskominfo has carried out are continuously optimizing in carrying out its online media strategy. It is trying to interact with residents of Depok's city and build a positive image by providing precise and clear information. Some of the obstacles faced in implementing the Cyber Public Relations of Depok City Diskominfo lie in the lack of Human Resources in managing the website, lack of coordination, and technical problems. Some of the obstacles faced in the Cyber Public Relations activities of the Depok City Diskominfo lie in the lack of Human Resources in conducting evaluations and lack of coordination in selecting specific targets.